Computational fluid dynamics study of airflow and particle deposition in diseased nasal airway - Riazuddin, Vizy Nazira (2018)
Understanding the properties of airflow in the nasal cavity is very important in determining the nasal physiology and in diagnosis of various anomalies associated with the nose. The complex anatomy of the nasal cavity has proven to be a significant obstacle in the understanding of nasal obstructive disorders. Due to their non-invasiveness, Computational Fluid Dynamics (CFD) has now been utilized to assess the effects of surgical interventions on nasal morphological changes as well as local breathing airflow characteristics through the upper airway of individual patients. Furthermore, nasal inhalation is a major route of entry into body for airborne pollutions. Therefore, the function of the upper airway to filter out the inhaled toxic particles is considered important. The determination of the total particle filtering efficiency and the precise location of the induced lesion in the upper airway is the first step in understanding the critical factors involved in the pathogenesis of the upper airway injury. The present work involved development of three-dimensional diseased upper airway models from Computed Tomographic (CT) scan images derived from a nasal airway without any nasal diseased and an upper airway which was diagnosed with chronic nasal obstruction and obstructive sleep apnea. Numerical simulation of airflow and transport and deposition of inhaled pollutant through chronic diseased nasal airway, constricted pharyngeal representing Obstructive Sleep Apnea (OSA) and diseased upper airway with OSA for pre- and post-operative cases have been studied. Detailed flow pattern and characteristics for inspiratory airflow for various breathing rates (7.5-40 L/min) were evaluated. Simulation of the particle transport and deposition of micro-sized particles with particle diameter ranging from 1-40 μm were also investigated. In the first part of this study, the surgical treatment performed in the nasal cavity which include septoplasty, inferior turbinate reduction and partial concha bullosa resection substantially increased nasal volume, which influenced flow partitioning and decreases the pressure drop and flow resistance of the nasal passage. The removal of the obstruction in the nasal airway significantly improve the breathing quality. However, the nasal airway experienced approximately about a 50 % decrease in total particle filtering efficiency after surgery. Therefore, careful consideration should be given to this matter before nasal operation especially for a patient with breathing allergic history. In the second part of this study, the morphology of the constricted pharyngeal representing OSA was found to significantly affect the airflow pattern and the deposition fraction of microparticles. The morphology of the upper airway, the size of the inhaled particle and breathing rate was found significantly affect the total particle deposition efficiency and local deposition fraction in the upper airway. The presented regional deposition fraction may be used in specifying the site of highest possibility for respiratory lesions according to the breathing rate and the size of the inhaled toxic particles. Results obtained from this study can be also used to estimate the location of airway obstruction in upper airway of patient with sleep apnea symptom. In the third part of this study, the surgical conducted procedure has cleared out the obstructions in the nasal airway hence improve the airflow distribution through the upper airway during inhalation process. This study shows that the nasal surgery alone can help improve the breathing quality in the upper airway with OSA. The reduction of the airflow resistance in the nasal cavity affect the pressure distribution in the lower part of the upper airway. Obstruction in the nasal passage and sudden airway expansion in the upper airway increased number of particles trap, recirculated and finally deposited in the airway. Finally, the experimental data obtained from the experimental study utilizing the developed pharyngeal airway further validate the result obtained from the numerical study.